2020
DOI: 10.1177/0022243720936230
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Synthetic Control Methods

Abstract: The authors propose a new Bayesian synthetic control framework to overcome limitations of extant synthetic control methods (SCMs). The proposed Bayesian synthetic control methods (BSCMs) do not impose any restrictive constraints on the parameter space a priori. Moreover, they provide statistical inference in a straightforward manner as well as a natural mechanism to deal with the “large p, small n” and sparsity problems through Markov chain Monte Carlo procedures. Using simulations, the authors find that for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The synthetic control method (SCM), developed by Abadie and Gardeazabal (2003) and Abadie et al (2010Abadie et al ( , 2015, uses a weighted average of outcomes of the controls to construct the counterfactual of treated units. Since its inception, a number of counterfactual models has been developed to extend it to multiple treated units (Ben-Michael et al, 2021a), staggered treatment (Gobillon and Magnac, 2016;Xu, 2017;Ben-Michael et al, 2021b), treatment reversal (Liu et al, 2021), nonparametric estimation of weights (Cerulli, 2019), spatial spillovers (Cao and Dowd, 2019;Grossi et al, 2020), and the Bayesian realm (Kim et al, 2020;Pang et al, 2022).…”
Section: Augmented Synthetic Control Methodsmentioning
confidence: 99%
“…The synthetic control method (SCM), developed by Abadie and Gardeazabal (2003) and Abadie et al (2010Abadie et al ( , 2015, uses a weighted average of outcomes of the controls to construct the counterfactual of treated units. Since its inception, a number of counterfactual models has been developed to extend it to multiple treated units (Ben-Michael et al, 2021a), staggered treatment (Gobillon and Magnac, 2016;Xu, 2017;Ben-Michael et al, 2021b), treatment reversal (Liu et al, 2021), nonparametric estimation of weights (Cerulli, 2019), spatial spillovers (Cao and Dowd, 2019;Grossi et al, 2020), and the Bayesian realm (Kim et al, 2020;Pang et al, 2022).…”
Section: Augmented Synthetic Control Methodsmentioning
confidence: 99%
“…Most studies document a sizable pass-through, between 59% and 103%, resulting in significant price increases for consumers (Cawley et al 2021) and significant drops in sales of taxed soda. Seiler, Tuchman, and Yao (2021) report a 46% reduction in volumes sold in Philadelphia; Powell and Leider (2020) find a 22% reduction in Seattle; Kim, Lee, and Gupta (2020) document a 6% reduction for Washington's short-lived soda tax; and mixed results emerge for Berkeley, including decreases ranging from 20% (Silver et al 2017) to 9% (Taylor et al 2019), though Rojas and Wang (2021) find no evidence of any effect. Extant research considers single locations and confounds regular price and promotional changes by assessing the price paid only, disregarding that consumers react differently to regular price and promotional price (Datta, Ailawadi, and Van Heerde 2017).…”
Section: Conceptual Foundationmentioning
confidence: 99%
“…The former includes tax introductions (e.g., soda taxes; e.g.,Seiler et al 2021;Kim et al 2020), the state of the economy (which includes raw material cost changes and its effect on marketing spending;Lamey et al 2012), and popular events (e.g., the Olympics;Keller, Deleersnyder, and Gedenk 2019). The latter captures events such as national-level boycotts (e.g.,Sun et al 2021) or industry-wide product-harm crises (e.g., Cleeren, Dekimpe, and Van Heerde 2017).6 It is important to recognize that we do not model retailer and soda brands as distinct strategic actors.…”
mentioning
confidence: 99%
“…A number of marketing studies make use of quasi-experimental data to estimate causal effects. Examples include studies of the effect of bookstore openings on sales at Amazon (Forman, Ghose, and Goldfarb 2009), the effect of TV advertising on online shopping (Liaukonyte, Teixeira, and Wilbur 2015), the effect of offline stores on online sales (Wang and Goldfarb 2017), and the effect of soda taxes on price and consumption (Kim, Lee, and Gupta 2020).…”
mentioning
confidence: 99%
“…Hahn and Shi (2017) show that the validity of any permutation-based approach requires a strong symmetry assumption that is unlikely to hold in quasi-experimental data and the violation of which leads to biased confidence intervals. Recently, some authors have suggested Bayesian alternatives to SC for regularization approaches (Kim, Lee, and Gupta 2020; Pang, Liu, and Xu 2022). The Bayesian approach solves the inference problem by allowing for the construction of credible intervals (of any quantity of interest) via simulation draws from the posterior distribution of model parameters.…”
mentioning
confidence: 99%